Erratum: BRAYAN PAIVA CAVALCANTE, CLÉCIO DANILO DIAS DA SILVA, EVER-TON HILO DE SOUZA, LEONARDO M. VERSIEUX, ADRIANA PINHEIRO MARTINELLI (2024) Hohenbergia alba and Hohenbergia sparsiflora, two striking new bromeliads from the Brazilian Atlantic Forest. Phytotaxa 665 (3): 233–242. - Cavalcante, Brayan Paiva; Silva, Clécio Danilo Dias Da; Souza, Everton Hilo De; Versieux, Leonardo M.; Martinelli, Adriana Pinheiro (Phytotaxa, 2024)
N/A